2019
DOI: 10.1177/1071100719873271
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Fixation Technique for Lisfranc Injuries

Abstract: Injuries to the Lisfranc complex range from purely ligamentous disruptions to fracture-dislocations of the tarsometatarsal joint. Treatment options include closed/open reduction with percutaneous pinning, open reduction and internal fixation (ORIF), and primary arthrodesis. We present a ligament reinforcement technique utilizing a flexible fixation device for the treatment of ligamentous Lisfranc injuries. Level of Evidence: Level V, expert opinion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…There were no problems encountered in our study with this accelerated postoperative protocol, and all athletes were able to return to full competition level. Similar to previous studies using suture button devices, 4 , 5 , 7 , 9 , 11 , 14 , 19 we did not encounter any wound problems, device loosening, failure of implants, recurrent instabilities, or loss of reduction in our patient group.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…There were no problems encountered in our study with this accelerated postoperative protocol, and all athletes were able to return to full competition level. Similar to previous studies using suture button devices, 4 , 5 , 7 , 9 , 11 , 14 , 19 we did not encounter any wound problems, device loosening, failure of implants, recurrent instabilities, or loss of reduction in our patient group.…”
Section: Discussionsupporting
confidence: 87%
“…We report a return to full weightbearing at 4 weeks postoperatively, compared with 12 weeks in Cho et al 8 and 6 weeks in several other case series using suture button stabilization. 4 , 14 , 19 , 37 Jain et al 19 and Charlton et al, 7 who also used a suture button stabilization system in elite athletes, reported returns to competition of 21 weeks and 26 weeks, respectively. It appears that the larger suture button device used in this series safely allowed earlier weightbearing than previous studies, allowing patients to return to competition much earlier, at 12 to 16 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of ligamentous Lisfranc injuries is always a controversial topic in clinics. Various operative strategies had been described such as closed/open reduction and percutaneous puncture with K-wires, open reduction and internal fixation with transarticular screws or plates, and primary arthrodesis [ 3 , 4 , 19 , 20 ]. Each of them had its own defects.…”
Section: Discussionmentioning
confidence: 99%
“…Low energy tarsometatarsal joint damage is often associated with purely ligamentous Lisfranc injuries. It is difficult to diagnose after injury because the position of Lisfranc ligament is deep [ 2 , 3 ]. Up to about 20–40% of ligamentous Lisfranc injuries are either mis-diagnosed or overlooked during initial evaluation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%